Assessing China’s Economic Prospects in the Context of Deflationary Trends - Zhang, Luyao (Transactions on Economics, Business and Management Research, 2024)
Consumer Price Index (CPI) is an crucial economic indicator which measures the changes in consumer prices and it reflects inflation. It is closely related to economic growth and its stability, and it’s influenced by both domestic factors and global factors. Each country could make effective economic policies with the help of CPI. This study delves into the intricate dynamics of the Consumer Price Index (CPI) in China, examining its temporal fluctuations and underlying factors. By analyzing historical data spanning multiple years, it uncovers trends in inflation rates, identifying both inflationary and deflationary pressures that shape the purchasing power of Chinese consumers. The analysis highlights key economic indicators influencing CPI variations, including commodity prices, monetary policy adjustments, supply chain disruptions, and global economic conditions. Furthermore, the study assesses the impact of these changes on various sectors and consumer segments, providing insights into the resilience and adaptability of the Chinese economy in the face of fluctuating price levels. Ultimately, this comprehensive examination aims to offer policy recommendations for maintaining price stability and fostering sustainable economic growth.